Penegakan Hukum terhadap PT Rayon Utama Makmur Akibat Limbah Tekstil yang Merugikan Warga - Widya Ayu Nirmala Sari (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2022)
Based on the 1945 Constitution Article 1 paragraph 3, Indonesia is a state ruled by law since the constitution of Indonesia incorporated several legal systems. The law should be fair, impartial to those in power and not intimidate the weak. However, the law is often misused and traded for the interests of those in power. This study aims to find out how the law is enforced against PT Rayon Utama Makmur that has harmed local residents for causing environmental pollution as a result of the textile factory activities. Data are collected from literature. The theory used is the conflict theory of Karl Marx given that there was a conflict of interest between PT Rayon Utama Makmur and the local residents. The results of the study indicate that the law enforcement against PT Rayon Utama Makmur is still very weak. After being proven to have polluted the environment by dumping the factory waste into the river thus endangering the health of the residents, PT Rayon Utama Makmur did not receive any significant sanctions so that it did not cause a deterrent effect for the company. The weak law enforcement for PT Rayon Utama Makmur caused injustice for the residents. And that gradually triggered a conflict between the residents and the company.